Estimation and Detection of Free Amino Acids from Ficus benghalensis Linn. - Shah, S.M.; Katade, S.R.; Deshmukh, M.R.; Naik, S.S.; Pendse, M.A.; Deshpande, N.R. (Asian Journal of Chemistry, 2016)
Detection of amino acids from various extracts of Ficus benghalensis was carried out by using different mobile phases and different chromatographic techniques. The results obtained were compared with standard amino acids in the respective mobile phases. The distribution of free amino acids in aerial roots and leaves of Ficus benghalensis showed the presence of some common amino acids. Aerial roots showed the presence of nine amino acids and the leaves showed presence of eight amino acids by paper chromatography. Eight amino acids in the roots and ten amino acids in the leaves were detected by performing silica gel coated aluminium TLC plate. The estimation of proteins from different extracts of the plant was also carried out spectrophotometrically.